2002
DOI: 10.1071/fp02012
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of nodulation in bean (Phaseolus vulgaris) by UV-B irradiation

Abstract: Exposure of bean plants grown in the greenhouse, where UV-B is low, to ambient levels of UV-B light stimulated nodulation more than 2.5-fold. Reduction of UV-B radiation to 3% of ambient levels for outdoor-grown plants through use of Mylar filters consistently reduced nodulation by 45%. The increase in nodulation caused by UV-B was mainly due to an increase in number and size of nodules. The amounts of UV-B-absorbing compounds in roots of UV-B-exposed plants increased almost 5-fold. However, the composition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Direct evidence of induction of NADP-malic enzyme by UV-B radiation was observed in leaves, stems and roots of three bean cultivars (Pinto et al, 2002). These results suggest that NADP-malic enzymes play an active role in plant defense responses against UV-B, possibly by providing NADPH for lignin and flavonoid biosynthesis.…”
Section: The Antioxidant Defense Systemmentioning
confidence: 62%
“…Direct evidence of induction of NADP-malic enzyme by UV-B radiation was observed in leaves, stems and roots of three bean cultivars (Pinto et al, 2002). These results suggest that NADP-malic enzymes play an active role in plant defense responses against UV-B, possibly by providing NADPH for lignin and flavonoid biosynthesis.…”
Section: The Antioxidant Defense Systemmentioning
confidence: 62%
“…Ambient UV-B affected the biomass partitioned to tubers and increased root diameter and root fresh weight of radish [30]. Pinto et al [13] found that bean plants grown in a greenhouse, where UV-B levels are low compared to outside levels had almost 60% more nodules per plant and 2.5-fold increases in nodulation compared to the plants grown outside. However, moderate and elevated UV-B exposure had no effect on the number of nodules, nodule mass and nodule size, although nitrogen concentration was markedly reduced in the roots of soybean and common bean [31].…”
Section: Discussionmentioning
confidence: 96%
“…Very little is known about the effects of ambient UV-B radiation on nitrogen metabolism. The number of nodules per plant in the bean grown in conditions of ambient UV radiation was higher than that on plants deprived of UV-B [13], and Chouhan et al [14] found that ambient UV-B reduced the number and size of nodules, total protein and Lb content in the soybean. However, Shiozaki et al [15] found that UV (300-400 nm) applied to leaves increased the amounts of nodulation and symbiotic N 2 fixation in pea plants.…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, all of irradiated seeds had higher number of root nodules at 150-250% of waterlogging compared to the initial line. According to Pinto et al (2002), irradiation exposure increases root nodule formation by 60%.…”
Section: Morphology Of Irradiated Soybean Plants In Waterlogging Condmentioning
confidence: 99%